Assessing Contrasting Approaches to Da'wah on Radio in Ilorin, Nigeria - Abdulwahab Danladi Shittu; Ibrahim Mubarak Olalekan (International Journal of Emerging Issues in Islamic Studies, 2023)
Contemporary scholars in Nigeria have duly acknowledged the significant role of electronic media in conveying the pure messages of Islam. Nevertheless, there exists variation in the approaches taken by advocates of Islam, resulting in diverse outcomes. This study undertook a comparative examination of two radio da'wah programs in Ilorin: "Madrasatud Dalilis Shar'i", hosted by Professor Abdulrahman Ahmad and "Manhaj Ahlus Sunnah wal Jama'a" hosted by Alfa Ali Jabata. The aim was to assess the relevance and impact of each program on the masses. Employing a combination of descriptive and comparative research methods, including interviews and observations, the study focused on selected episodes. The relevance of the programs was derived from the examination of the two programs while the impact assessment involved considering audience feedback and listener engagement. The findings indicate that "Manhaj ahlus Sunnah wal Jama'a" adopts a predominantly satirical tone, whereas "Madrasatud Dalilis Shari" maintains an academic approach. In light of these observations, the study recommends that effective da'wah activities should strike a balance between being mild and academic and should not be sataric. This objective could be realized through the establishment of an institution in Ilorin to regulate da'wah practices. This institution, ideally comprising a committee of experts in the field, would require government support to ensure its effectiveness.